Características y génesis de los yacimientos nucleares "Dr. Braulies" y "Los Reyunos", Departamento de San Rafael, Provincia de Mendoza - Nicolli, Hugo B.; Chaar, Edmundo; Latorre, Carlos O. (Academia Nacional de Ciencias de Córdoba, 1973)
Fil: Nicolli, Hugo B. Comisión Nacional de Energía Atómica; Argentina